The Nutrient Potency of Palm Oil Plantation and Mill’s By-product Processed with Amofer Technology as Ruminant Feed - Hamdi Mayulu (Chemical Engineering Diponegoro University, 2014)
By-product derived from palm oil plantation and mill is very potential for energy and protein source for ruminant feed. However, it is still underutilized due to low content of crude protein (CP) with high crude fiber (CF). Ammoniation or fermentation technology could optimize the quality of by-product by increasing digestibility, reducing CF and increasing CP content. The objective of this research was to determine the nutrient and potency value of palm oil plantation and mill’s by-product applied with amofer technology for ruminant feed. Sample was prepared in two methods: 1) sample without amofer application, 2) sample with amofer application under anaerobic method and incubated for 18 days. Ammoniation was carried out by adding urea of 3% from the total material and then incubated for nine days. At the ninth day, some microorganisms starter i.e. cellulolytic, amillolytic and proteolytic were added by 1% of the total material. Proximate analysis was carried out in laboratory to examine the nutrient value. The crude protein content at each part of feed material before and after amofer treatment was follow: palm midrib: 3.16%:17%; palm leaves 6.53%:26.51%; empty fruit bunch 7.01%:1673%; palm pressed fiber 5.56%:16.00%. While the crude fiber at each part of feed material was: palm midrib 37.85%:30.86%; palm leaves 30.39%:24.41%; EFB 40.22%:34.98%; PPF 50.39%: 41.70%. The application of amofer could increase the amount of feed material (ton/ha/y): dry matter (DM) 14.82:15.89; CP 0.79:2.87; total digestible nutrient (TDN) 7.63:8.5. Moreover, amofer application could also increase the nutrient content of palm oil plantation and mill’s by-product by increasing CP and reducing CF. This increasing was also followed by the increasing of DM, CP, and TDN which indicated that those feed sources were recommended as ruminant feed material